2020
DOI: 10.1088/2631-8695/abcd0e
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of efficient Electromagnetic Linear actuators for flapping wing MAVs

Abstract: A constraining factor in the development of flapping wing micro air vehicles (MAVs) is the power density and efficiency of actuators. Piezoelectric and rotary electromagnetic actuators have been shown to have functional power densities but can require mechanically complex transmissions to create flapping motion. Electromagnetic Linear actuators (ELAs) have unique characteristics, allowing them to be controlled and implemented similarly to muscles but demonstrated much lower efficiency. This study presents conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Actuator configurations have typically consisted of a single magnet and coil as shown in Figure 13, left. Our recent work has looked at the performance of actuators with multiple magnets and coils shown in Figure 13, right [114]. These actuators utilise two magnets with axially opposing magnetic fields.…”
Section: Actuationmentioning
confidence: 99%
See 1 more Smart Citation
“…Actuator configurations have typically consisted of a single magnet and coil as shown in Figure 13, left. Our recent work has looked at the performance of actuators with multiple magnets and coils shown in Figure 13, right [114]. These actuators utilise two magnets with axially opposing magnetic fields.…”
Section: Actuationmentioning
confidence: 99%
“…Tuning this system reduced the power consumption by a factor of 7, from 15 kW/kg [113] (relative to the mass of the craft) to 2 kW/kg. Further modifications of the actuator shown in [114] have demonstrated that, for a fixed mass, an improved design in conjunction with operating at the natural frequency of the system can bring the power-to-weight ratio to between 910 and 260 W/kg. Resonant linear electromagnetic actuators can achieve an efficiency of over 15% at the milligram scale, equivalent to Drosophila melanogaster flight muscles, where power output is approximately 60 W/kg for sustained flight with muscle efficiency of around 10% [118].…”
Section: Actuator Modellingmentioning
confidence: 99%